Additive-free electrode fabrication with reduced graphene oxide using supersonic kinetic spray for flexible lithium-ion batteries. (November 2018) - Kim, Seong Dae; Lee, Jong-Gun; Kim, Tae-Gun; Rana, Kuldeep; Jeong, Jong Yeob; Park, Jong Hyeok; Yoon, Sam S.; Ahn, Jong-Hyun
Abstract: Thin, lightweight, and flexible lithium-ion batteries (LIBs) are emerging as a promising power source for high-performance flexible electronics. However, their technological drawbacks have hindered the development of fully flexible electronics because of a lack of reliable electrode materials that combine superior electrochemical properties with mechanical flexibility. As a solution to this problem, we herein demonstrate an additive-free electrode fabrication process, where reduced graphene oxide (rGO) is coated onto a current collector using a supersonic kinetic spray technique (spray-rGO). The spray-rGO demonstrates outstanding mechanical and electrochemical properties compared to those of rGO electrodes fabricated using the conventional process. Moreover, despite being fabricated without any binders, spray-rGO exhibits high adhesion energy, which enables the fabrication of highly flexible electrodes with no structural deterioration or capacity degradation. This approach to fabricate additive-free flexible electrodes, which results in electrodes that satisfy other important criteria such as high rate capability, long-term cyclability, and facile and fast fabrication, is a prospective method for developing high-performance flexible LIBs. Graphical abstract: Image 1